Empathy in Paediatric Postgraduate Trainees: The Gender Effect - Zia, Alina; Wajid, Gohar; Zia, Aiza; Zia-ul-Miraj, Mohammad; Waqar, Ammara; Mahmood, Hamid (British Journal of Healthcare and Medical Research, 2025)
Empathy is a key element of patient-physician relationship. Higher empathy levels are associated with better clinical outcome. Gender differences have been observed in prior international studies. The purpose of this study was to explore the empathy levels among the male and female postgraduate trainee residents in Paediatrics in Pakistan. This study involved 129 postgraduate trainee residents in Paediatrics. The participants anonymously completed the Jefferson Scale of Empathy (HP-Version). The data were analysed by SPSS 20. Comparison of empathy score between males and females was carried out by the independent sample t-test. The mean empathy score was 102.75. Females had significantly higher empathy levels than males (105.22 vs. 99.43). The gender difference was statistically significant (p=0.028). The male residents were significantly less empathic than males. Targeted educational activities are recommended to sustain and enhance empathy during postgraduate training.